ADAMTS12 Depletion by Insulin in OUMS-27 Human Chondrosarcoma Cells - Aynur ALTUNTAŞ; Sümeyya AKYOL; Bahattin ADAM; Özlem ÇAKMAK; Veli UĞURCU; Gönül ERDEN; Yunus YÜKSELTEN; Kadir DEMİRCAN (Archives of Rheumatology, 2015)
Objectives: In this study, we aim to investigate the association between articular damage in diabetes and a disintegrin-like and metalloproteinase with thrombospondin motifs 12 (ADAMTS12) at gene expression and protein levels. Materials and methods: OUMS-27 human chondrosarcoma cells were used to investigate how ADAMTS12 levels changed in vitro condition in presence and absence of insulin. The study included three groups of cells treated with 10 μg/mL of insulin, and a control group. Cells were incubated with insulin in medium for one day, three days, and seven days. The effects of insulin on ADAMTS12 were investigated at both gene expression and protein levels. The relationships between the variables were tested by Mann-Whitney U test. Results: ADAMTS12 expression was significantly lower in the groups treated with insulin medium for one day and seven day periods (p=0.008 and p=0.008, respectively) compared to the control group. No significant difference was detected in the expression level between the groups kept in insulin medium for three days and the control group (p=0.55). In addition, protein amounts of the groups exposed to insulin medium for one, three, and seven day periods were lower. Conclusion: Insulin reduces the amount of ADAMTS12 which causes delayed recovery of cartilage tissue in the OUMS-27 cell lines utilized in our study for their chondrocytic properties. This reduction due to insulin treatment may contribute to recovery of cartilage tissue.